PEMBELAJARAN BERBASIS BUDAYA DAN PEMBENTUKAN IDENTITAS LOKAL PADA SISWA SEKOLAH DASAR - Sri Sugiyarti; Alpendi; Diah Rina Miftakhi (Edutainment : Jurnal Ilmu Pendidikan dan Kependidikan, 2026)
In an era of rapid globalization, preserving local cultural identities has become a crucial educational challenge, particularly for primary school students undergoing early identity formation. This study investigates the process of strengthening local identity among primary school students through culture-based learning in Sleman Regency, Special Region of Yogyakarta, Indonesia. Using a qualitative exploratory case study design, data were collected through classroom observations, interviews with teachers, students, and school principals, and document analysis in five public primary schools recognized for culture-based education initiatives. The findings reveal that integrating Javanese cultural elements—such as language, arts, traditional attire, culinary heritage, and community rituals—into formal education, experiential learning, extracurricular activities, and immersive school environments effectively fosters students' cultural pride, belonging, and identity resilience. The study underscores the critical role of culturally responsive education in countering the homogenizing effects of globalization and maintaining cultural sustainability. However, it also identifies challenges such as resource limitations and the need for stronger community engagement to ensure the sustainability of culture-based learning programs. These findings provide valuable insights for educators and policymakers aiming to design culturally integrated curricula that nurture both local identity and global competence among young learners.